1988
DOI: 10.1073/pnas.85.9.3071
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of haplotypes leads to biased estimates of admixture proportions in human populations.

Abstract: A population formed by genetic admixture of two or more source populations may exhibit considerable linkage disequilibrium between genetic loci. In the presence of recombination, this linkage disequilibrium declines with time, a fact that is often ignored when considering haplotypes of closely linked systems Admixture analysis in human populations traditionally uses polymorphic genetic markers. Careful reviews of the subject indicate that the precision and utility of admixture analysis can be greatly enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Here, we refer to such gametic association as "mixture disequilibrium" to distinguish it from gametic association between closely linked loci. Such mixture disequilibrium will decay over time, but (2) showed that in the presence of recombination, estimates of admixture from haplotype data may be errorprone, if the genetic assay of the admixed population is not done immediately after the admixture event. There are many instances where human populations have been formed through admixture of the same two stocks of racial groups, yet the degree of admixture varies among the admixed groups (with approximately the same historical depth of admixture).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we refer to such gametic association as "mixture disequilibrium" to distinguish it from gametic association between closely linked loci. Such mixture disequilibrium will decay over time, but (2) showed that in the presence of recombination, estimates of admixture from haplotype data may be errorprone, if the genetic assay of the admixed population is not done immediately after the admixture event. There are many instances where human populations have been formed through admixture of the same two stocks of racial groups, yet the degree of admixture varies among the admixed groups (with approximately the same historical depth of admixture).…”
mentioning
confidence: 99%
“…Under these assumptions, it is known (2,4) that the mixture disequilibrium between the A and B loci in the admixed population Z, produced by admixture, at generation 0 can be written as [1] where 8A Thus, for given values of 8A and 8B (allele frequency differences between the two parental populations) and mixture Abbreviation: lod, log-likelihood ratio.…”
mentioning
confidence: 99%
“…As previously discussed, a consequence of PS in association studies is the potential for bias in the estimate of allelic associations due to deviations from the HardyWeinberg equilibrium and the induction of linkage disequilibrium [156,157] . In order for bias due to PS to exist, both the frequency of the marker variant of interest and the background disease prevalence must vary significantly by race/ethnicity [158,159] .…”
Section: Association Testing Methods For Population-based Data Using mentioning
confidence: 99%
“…Association studies that depend on LD between markers and disease genes have helped to decipher some genetic basis of differential susceptibility to complex diseases (e.g., Feder et al 1996). Regular association studies, usually, case-control analyses in unrelated cases and controls may suffer inflated type I errors (Chakraborty and Smouse 1988;Lander and Schork 1994;Weir 1996;Spielman and Ewens 1996) that have not been quantified until recently (Deng and Chen 1999;Deng et al 2001a). In addition, population admixture/stratification may mask or reverse true genetic effects in classical association studies (Deng 2001).…”
Section: Introductionmentioning
confidence: 96%